Design and tri-objective optimization of a hybrid efficient energy system for tri-generation, based on PEM fuel cell and MED using syngas as a fuel. (25th March 2021) - Fakhari, Iman; Behzadi, Amirmohammad; Gholamian, Ehsan; Ahmadi, Pouria; Arabkoohsar, Ahmad
Abstract: This article presents a novel solution to enhance the performance and cost-effectiveness of a biomass-based proton exchange membrane (PEM) fuel cell. It investigates the proposed configuration from energy, exergy, economic, and environmental aspects. The idea is conducted by the integration of the proposed system with a gasifier, a multi-effect desalination (MED) unit, and a series two-stage organic Rankine cycle (STORC) using various zeotropic mixtures for the use of waste heat for heat, power, and freshwater production. A comparative parametric study is carried out not only to evaluate the effect of main parameters on the performance of the proposed system but also to determine the best zeotropic mixture from different standpoints. In addition, the tri-objective optimization using a genetic algorithm approach is implemented to the system to ascertain the best operating condition to minimize the total cost rate and maximize the exergy efficiency and the produced fresh water simultaneously. The results of a comparative parametric study reveal the superiority of R601a-C2 Butene (75%–25%) among various STORC working fluids from thermodynamic and economic points of view. The results further show that the proposed integrated system has a considerably lower CO2 index compared to the same system without the STORC unit. For the final tri-objective optimization point, while the minimum total cost rate is 64.91 $/h, the maximum exergy efficiency and produced freshwater are 23.43% and 162.86 m 3 /day, respectively. Furthermore, the scatter distribution of the main decision variable reveals that moisture content and current density are not a sensible variable, and their optimal points are distributed in the whole domain.